2021
DOI: 10.1021/acs.langmuir.1c02751
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Sodium Alginate–Sodium Borate Hybrid Binders for High-Capacity Silicon Anodes in Lithium-Ion Batteries

Abstract: Silicon is considered one of the most promising next-generation anode materials for lithium-ion batteries. It has the advantages of high theoretical specific capacity (4200 mAh·g–1), which is 10 times larger than that of a commercial graphite anode (372 mAh·g–1). However, there are some problems such as the pulverization of the electrode and an unstable solid electrolyte interphase (SEI) layer aroused by the huge bulk effect (>300%) of Si during the repeated lithiation/delithiation process. A binder plays a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The SEI film of the PI-COOH binder electrode remained stable, so R SEI and R CT remained at a low level, providing relatively stable electrochemical and cycling performance. However, the PI binder electrode is difficult to form a stable SEI film, which leads to the consumption of electrolyte, the continuous growth of SEI, and the lithium dendrite on the surface of the lithium foil, which seriously degrades the battery performance as shown in Figure …”
Section: Results and Discussmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEI film of the PI-COOH binder electrode remained stable, so R SEI and R CT remained at a low level, providing relatively stable electrochemical and cycling performance. However, the PI binder electrode is difficult to form a stable SEI film, which leads to the consumption of electrolyte, the continuous growth of SEI, and the lithium dendrite on the surface of the lithium foil, which seriously degrades the battery performance as shown in Figure …”
Section: Results and Discussmentioning
confidence: 99%
“…To meet the ever increasing demands of portable electronics requirement for higher energy and power densities, high-performance materials development is imperative for lithium-ion batteries (LIBs). Silicon anode materials show the brightest future owing to their super high theoretical capacity (4200 mAh g –1 for Li 22 Si 5 ), relatively low discharge potential (∼0.4 V versus Li + /Li), and rich abundance in the earth. Nevertheless, the commercial application of silicon anode materials is still hindered with the challenges related to the huge volume expansion. The solid electrolyte interface (SEI) and electrode structure are damaged due to tremendous volume change of silicon anode materials during Li + lithiation and delithiation processes, which seriously deteriorate the lifespan of the lithium-ion battery. Various strategies have been adopted to ameliorate these issues, such as controlling the morphology of silicon anode materials, using late-model electrode structures, and employing high-performance binders. …”
Section: Introductionmentioning
confidence: 99%
“…However, the huge volume expansion of Si anode during repeated lithiation/delithiation process can lead to LIBs with low cycle life. [179] To solve such problems, Li et al [180] condensed the inorganic cross-linker sodium borate with the commonly used binder sodium alginate through an esterification reaction to obtain the product (SA-SB) with high mechanical properties and peel strength (as shown in Figure 15a,b). Electrochemical test results showed that since SA-SB binder helped to maintain the structural stability of the Si anode during long cycling, the capacity retention of the Si anode using the SA-SB binder was 64.1% at a current density of 0.2 A g −1 after 100 cycles, while the SA-SB binder could promote the formation of stable SEI film, thus further improving the CE.…”
Section: Bindermentioning
confidence: 99%
“…Schematic diagram of a) synthesis of SA-SB binder,and b) mechanical properties of SA-SB binder. Reproduced with permission [180]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%
“…Furthermore, water-soluble binders (such as CMC, poly­(vinyl alcohol) (PVA), etc. ) have privileges in expanding their application toward advanced Si anodes with huge volume expansion. Ascribed to the abundant carboxylic or hydroxyl groups, these binders, different from PVdF, intensively interact with the Si particles and thus efficiently buffer the volume changes of the material, which hence results in enhanced cycle performances.…”
Section: Introductionmentioning
confidence: 99%